Performance enhancement of high-temperature polymer electrolyte membrane fuel cells using Pt pulse electrodeposition - Kim, Don Kwon; Kim, Hoyoung; Park, Hyanjoo; Oh, SeonHwa; Ahn, Sang Hyun; Kim, Hyoung-Juhn; Kim, Soo-Kil (ELSEVIER, 2019)
The development of high-performance polymer electrolyte membrane fuel cells that operate at elevated temperatures is urgently required to overcome the technical problems associated with operation at low temperatures. Here, we report an effective way to enhance electrode performance via simple Pt pulse electrodeposition at room temperature. This electrodeposition process enables both the formation of additional Pt electrocatalysts with extremely low loading (i.e., similar to 0.05 mg cm(-2) for 100 pulse cycles) as a function of pulse number and control of the wetting properties of commercial Pt-based electrodes. Following optimization of the electrode conditions and configurations, the controlled hydrophilicity of the anode enhances the phosphoric acid distribution and the formation of a triple phase boundary in the catalyst layer, resulting in lowered ohmic and charge transfer resistances, respectively. The mass activities of the membrane electrode assembly with the anode modified by Pt pulse electrodeposition is 437.2 mW mg(Pt)(-1) (H-2/O-2), which is approximately 1.36 times higher than that of the pristine membrane electrode assembly. The controlled hydrophilicity allows moderate improvement of the performance, even without additional Pt. The results presented herein demonstrate the importance of surface property control for electrode preparation to achieve enhanced performance of high-performance polymer electrolyte membrane fuel cells.
Keywords: OXYGEN REDUCTION REACTION; PHOSPHORIC-ACID; CATALYST LAYERS; PEMFC; WATER; CATHODE; DESIGN; DEGRADATION; ALLOY; DEHYDRATION